Synthesis of water-soluble and thermoresponsive phthalocyanine ended block copolymers as potential photosensitizer - Li, YanHui; Zhao, Dehai; Li, Yanwei; Liu, Yongzhe; Duan, Qian; Kakuchi, Toyoji (Dyes and Pigments, 2017)
A novel zinc(II) tetraaminophthalocyanine ended block copolymer methoxypolyethylene glycol-b-poly(N-isopropylacrylamide) (MPEG-b-PNIPAAM-ZnTAPc) had been synthesized through an easy way. First, the diblock copolymers MPEG-b-PNIPAAM were synthesized by atom transfer radical polymerization (ATRP) and functionalized with one molecule of maleic anhydride (MA) by ATRP, and then reacted with ZnTAPc to form a water-soluble and thermoresponsive photosensitizer. The lower critical solution temperatures for the copolymers can be easily controlled by changing the ratio of MPEG and PNIPAAM. In aqueous solution, the thermosensitive copolymers will self-assemble into micelles and characterized by dynamic light scattering and transmission electron microscopy, and the sizes of micelles will increase with temperature increasing. In the micelles, ZnTAPc will aggregate to induce fluorescence quenching. As a photosensitizer, MPEG-b-PNIPAAM-MA-ZnTAPc can generated singlet oxygen species with good quantum yields (ΦΔ = 0.23), which were believed to be the major reactive oxygen species. And the copolymer had low dark cytotoxicity and high phototoxicity based on MTT assay, so the MPEG-b-PNIPAAM-ZnTAPc will used in the field of photodynamic therapy and photocatalytic oxidation. [Display omitted] •MPEG-b-PNIPAAM was functionalized with one maleic anhydride by ATRP to react with ZnTAPc to form MPEG-b-PNIPAAM-ZnTAPc.•The LCST for MPEG-b-PNIPAAM-ZnTAPc can be easily controlled by changing the ratio of MPEG and PNIPAAM.•The sizes of micelles formed by MPEG-b-PNIPAAM-ZnTAPc will increase with temperature increasing.•As a photosensitizer, MPEG-b-PNIPAAM-MA-ZnTAPc can generated singlet oxygen species with good quantum yields.